Software Defined Radio Design for OFDM Based Spectrum Exchange Information Using Arduino UNO and X-Bee - Arief Marwanto; Sharifah Kamilah Syed Yusof; Muhammad Haikal Satria (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
A cost expenditure of software defined radio software has limiting the development of cognitive radio in third countries. Moreover, a complexity of signal processing library in a SDR platform has contributed to the hard implementation in real applications. In this works, the development of SDR platform with low cost expenditure is proposed. Arduino UNO and X Bee uses for the OFDM based spectrum exchange information. In a case of spectrum sensing scenario, the objective of the local spectrum sensing is to detect the PU’s signal detection. The performance of SN ability to sense the PU’s signal is crucial. It was shown that from the previous works as the detected power is quantized into information bit is simulated.  In  order  to  implemented  the  spectrum exchange  information during  sensing,  Arduino  UNO  and  X  Bee  is implemented to sense the presence of PU activity channels of wifi terminals based on the energy of the signals. The detected power (RSSI) of wifi terminals is exchanged into an OFDM subcarrier tone signal such as orthogonal sub-channel that being equally divided from the licensed band.   The results shows that using proposed software defined radio (SDR) based on Arduino and X Bee, the cognitive radio spectrum sensing is applied. The received power from the PU’s channels such as wifi networks can be detected as well. The system could received and exchanged into OFDM-based subcarrier information bits.